When water saving limits recycling: Modelling economy-wide linkages of wastewater use. (1st January 2016) - Luckmann, Jonas; Grethe, Harald; McDonald, Scott
Abstract: The reclamation of wastewater is an increasingly important water source in parts of the world. It is claimed that wastewater recycling is a cheap and reliable form of water supply, which preserves water resources and is economically efficient. However, the quantity of reclaimed wastewater depends on water consumption by economic agents connected to a sewage system. This study uses a Computable General Equilibrium (CGE) model to analyse such a cascading water system. A case study of Israel shows that failing to include this linkage can lead to an overestimation of the potential of wastewater recycling, especially when economic agents engage in water saving. Highlights: Cascading water use by different economic agents is introduced in a CGE model. Considering cascading water use is crucial if the sewage recycling rate is high. A measure to estimate the shadow price of sewage is provided. Endogenous price adjustments allow to balance wastewater supply and demand.